2021
DOI: 10.3389/fmed.2021.606755
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic: Advances in Diagnosis, Treatment, Organoid Applications and Impacts on Cancer Patient Management

Abstract: Coronavirus disease 2019 (COVID-19) caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread globally and rapidly developed into a worldwide pandemic. The sudden outburst and rapid dissemination of SARS-CoV-2, with overwhelming public health and economic burdens, highlight an urgent need to develop effective strategies for the diagnosis and treatment of infected patients. In this review, we focus on the current advances in the diagnostics and treatment for SARS-CoV-2 infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 191 publications
(235 reference statements)
0
6
0
Order By: Relevance
“…However, in another study, opposing results indicated that IFN upregulated the expression of ACE2 and thus promoted SARS-CoV-2 infection. We speculated that IFN might play a two-tier role in the infection of lungs by SARS-CoV-2 [ 126 ]. DPP-4 is a transmembrane glycoprotein that might also act as a potent receptor of SARS-CoV-2.…”
Section: Organoids Remodel the Research On Drug Screening And Vaccine...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in another study, opposing results indicated that IFN upregulated the expression of ACE2 and thus promoted SARS-CoV-2 infection. We speculated that IFN might play a two-tier role in the infection of lungs by SARS-CoV-2 [ 126 ]. DPP-4 is a transmembrane glycoprotein that might also act as a potent receptor of SARS-CoV-2.…”
Section: Organoids Remodel the Research On Drug Screening And Vaccine...mentioning
confidence: 99%
“…The antibody blocked the binding of the spike protein to ACE2 receptors on host cells, whereas the peptide inhibited viral binding to the DPP-4 receptor [ 127 ]. A number of antineoplastic drugs were evaluated by Ye and his colleagues, who indicated that bevacizumab, thalidomide, and imatinib might alleviate symptoms in patients with severe COVID-19 [ 126 ]. Remdesivir was also considered to be more efficient than a placebo for the treatment of hospitalised patients with COVID-19; it prevented the progression of respiratory disease, leading to faster recovery [ 128 ].…”
Section: Organoids Remodel the Research On Drug Screening And Vaccine...mentioning
confidence: 99%
“…The clinical characteristics of COVID-19 that were identified in cancer patients, as well as the possible influence of cancer and anticancer intervention on patients' immune responses to SARS-CoV-2. Viral infections are more likely to impact cancer patients, and care should be made to cure them, along with the physiological interrelationship between two illnesses and practical recommendations for the delivery of anticancer drugs in infected patients with coronavirus [ 197 ]. Cancer patients are at a greater risk for COVID-19 and consequences such as hospitalization, critical care, and mortality, compared with the general population, due to metabolic problems such as diabetes and hypertension, as well as systemic immunosuppression.…”
Section: Complications Associated With Covid-19mentioning
confidence: 99%
“…Patients with COVID-19 lung cancer may have critical anoxia and develop more quickly because of poor baseline lung function and tolerance [ 205 ]. Tocilizumab, a genetically engineered monoclonal antibody that works as an anti-IL-6-receptor inhibitor, is used to cure COVID-19 individuals with cytokine release syndrome because it lowers COVID-19 morbidity and death, even in cancer patients [ 197 , 206 ].…”
Section: Complications Associated With Covid-19mentioning
confidence: 99%
See 1 more Smart Citation